Quinone azine organic electrode material with multiple active sites and preparation method and application thereof
The preparation of conjugated quinazine organic electrode materials through amidation reaction and supercritical fluid method solves the problem of low capacity utilization and circulation performance of aqueous zinc ion battery electrode materials, and achieves efficient electrochemical performance and stability. High-efficiency energy storage application of aqueous zinc ion batteries.
Patent Information
- Application Number
- CN202411324448.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-23
AI Technical Summary
The capacity utilization and circulation performance of existing water-based zinc-ion battery electrode materials are low, and inorganic materials have problems such as resource shortage, environmental pollution and structural collapse. The quinone organic electrode materials have insufficient anti-dissolution ability, resulting in high-efficiency energy storage. Poor performance in application.
Amidation reaction and supercritical fluid method were used to prepare conjugated quinazine organic electrode materials with multiple redox active sites and uniform large π conjugated structures. By synthesizing benzo[b]quinoxaline[2,3- i]Phenazine-6,8,13,15-tetraketone and other compounds improve electrochemical properties and material stability.
It has achieved excellent specific capacity, material utilization and rate performance of aqueous zinc ion batteries, significantly improved circulation performance and stability, and has broad application prospects.
Smart Images

Figure CN119219642A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of aqueous metal ion battery electrode materials, and in particular relates to a quinonezine organic electrode material with multiple active sites, a preparation method and an application thereof. Background Art
[0002] In the past two decades, the rapid increase in fossil energy consumption and its negative impact on the environment have prompted people to explore renewable energy and more efficient energy storage technologies. These rapidly growing demands have promoted the development of high-performance energy storage batteries. Lithium-ion batteries have extremely high energy density, excellent cycle performance, and excellent voltage platform. Once commercialized, they quickly occupied the energy storage device market. However, the organic electrolytes used in lithium-ion batteries are toxic, costly, and have limited resources, which cannot meet the huge market demand. Aqueous zinc-ion batteries have become a hot topic of research due to their inherent safety, high theoretical capacity, and environmental friendliness.
[0003] At present, the research on electrode materials for aqueous zinc-ion batteries is mainly focused on inorganic materials, which have advantages such as high capacity, high energy density and high power density, but at the same time they also have many problems, such as resource shortage, environmental pollution, complex synthesis and high process energy consumption. In addition, due to the rigid structure of inorganic materials, the insertion / extraction of cations during the cycle will lead to volume expansion and phase change, and even structural collapse in severe cases, resulting in capacity decay. These problems make it difficult to achieve a higher level of breakthrough in the performance of inorganic materials used in electrodes.
[0004] Compared with non-electrode materials, the synthesis process of organic materials is simple and easy, easy to mass produce, and relatively low in cost. At the same time, the structure of organic materials is diverse, and their electrochemical performance can be improved through simple molecular engineering modification. According to the different active sites, commonly used organic electrode materials can be divided into two categories: quinones and imines. Quinone materials have stable performance, low price, abundant resources, high discharge capacity and low polarizability, but quinone small molecules are easily soluble in organic electrolytes, which will affect their cycle stability. Wang's team found that the pyrene-4,5,9,10-tetraketone (PTO) cathode with a tetracarbonyl group and a planar conjugated structure has a high current density of 0.04A g -1 336mAh g -1 The specific capacity of 3Ag -1After 1000 cycles at a current density of 1.50 Å, the battery has a capacity retention rate of 70% (Angew. Chem. Int. Ed. 57, 11737–11741 (2018).). The lone pair of electrons in nitrogen atoms in imide-based materials can improve redox activity and improve dissolution resistance, but they are inherently limited in structural design and have great limitations for studying higher capacity materials. Huang et al. used 1,4,5,8-naphthalene diimide (NDI) layered molecules as cathodes with a capacity of only 200 mAh g -1 [J.Power Sources 482,228904(2021)]. Wang et al. found that the imine material TAP / Ti 3 C 2 The Tx cathode delivers 303 mAh g at a current density of 0.04 Ag-1 -1 reversible capacity[Adv.Mater.34,2206812(2022).].
[0005] In order to improve the anti-dissolution ability of quinone materials, new active groups were added. Nitrogen active compounds are widely used as electrochemically active materials because of their rich storage sites and large insoluble frameworks. The electronegativity of N is between that of C and O, which can not only improve electronic conductivity but also increase redox potential. In recent years, more and more materials have both electroactive carbonyl and imine groups in their molecular structures. Such materials are called quinonezines. The carbonyl and imine groups in the structure of quinonezines have similar redox mechanisms and potentials. Integration in the same conjugated system is an effective strategy to improve theoretical capacity or redox potential or both. The fusion of quinone molecules with pyrazine units can extend the number of aromatic core units, thereby reducing molecular solubility and increasing specific capacity. However, existing quinonezines have the disadvantage that the active sites are too dense, resulting in insufficient capacity utilization. For example, the quinonezine structure BBQPH proposed by Liu et al. has a theoretical specific capacity of 567 mAh g -1 , but the actual specific capacity is 490mAh g -1 , the material utilization rate is only 86.4%, and the cycle performance is weak, which needs to be further improved (Nat. Commun. 14, 5235 (2023)). Summary of the invention
[0006] The object of the present invention is to provide a preparation method and application of a conjugated quinone-based organic electrode material having uniformly dispersed multiple redox active sites, diversified structures and stability. The raw materials of the material are easily available, the synthesis method is simple, easy to scale up, and the yield is high. At the same time, the material provides multiple electrochemical active sites and a uniform large conjugated structure system, which can solve the shortcomings of low capacity and utilization rate of existing organic electrode materials and has broad application prospects.
[0007] The conjugated quinone organic electrode material provided by the present invention has uniformly dispersed multiple redox active sites, diversified structures and is stable and is selected from one of benzo[b]quinoxalino[2,3-i]phenazine-6,8,13,15-tetraketone (I), pyrazino[2,3-b:5,6-b']dibenzo-6,17-dione (II) and 6a,20a-pyrazino[2,3-b]pyrazino[2',3':6,7]quinoxalino[2,3-i]phenazine-6,8,10,17,19,21-hexanone (III):
[0008]
[0009] The present invention also provides a method for preparing a conjugated quinonezine organic electrode material: firstly, an amidation reaction is used to obtain an intermediate product, and then an oxidation method is used under a supercritical state to obtain a quinonezine organic electrode material having multiple active sites;
[0010] The preparation method of the intermediate product is: preparing the intermediate product by amidation reaction of dihydroxyphenazine and o-phenylenediamine derivative or amidation reaction of dihydroxyphenazine and 2,3-diaminophenazine.
[0011] The preparation steps of synthesizing conjugated quinone-based organic electrode materials using dihydroxyphenazine and o-phenylenediamine derivatives are as follows:
[0012] (1) First, commercial naphthoquinone derivatives and potassium salt of phthalimide are used as raw materials, acetonitrile solution is added, and the mixture is stirred and refluxed for 12 hours under a nitrogen atmosphere. After hot filtration and washing, hydrazine hydrate is added for reduction, and solid o-phenylenediamine derivatives are obtained after washing and vacuum drying.
[0013] The molar ratio of the naphthoquinone derivative to the potassium salt of phthalimide is 1:2-1:4.5, and the naphthoquinone derivative is selected from 2,3-dichloro-1,4-naphthoquinone or tetrachloronaphthoquinone.
[0014] (2) Weigh o-phenylenediamine and p-hydroxybenzoquinone, then add H 2 O as solvent, heat the mixture to 110°C under nitrogen atmosphere, and reflux and stir continuously for 10-12h. After the reaction is completed, cool to room temperature, remove the solvent by suction filtration, wash with water, and vacuum dry to obtain a black powder, i.e., dihydroxyphenazine.
[0015] The molar ratio of o-phenylenediamine to p-hydroxybenzoquinone is 1:1 to 1:1.5.
[0016] (3) using the dihydroxyphenazine prepared in step (2) and the o-phenylenediamine derivative prepared in step (1) as raw materials, grinding until fully mixed, and heating at 200 to 400° C. for 4 to 6 hours to obtain an intermediate product;
[0017] The molar ratio of dihydroxyphenazine to o-phenylenediamine derivative is 1:1 to 1:1.5;
[0018] (4) The supercritical fluid method was used to prepare conjugated quinonezine organic electrode materials.
[0019] The preparation steps of synthesizing quinone-based organic electrode materials by reacting dihydroxyphenazine and 2,3-diaminophenazine are as follows:
[0020] (1) Dissolve o-phenylenediamine in water and add ferric chloride in a molar ratio of 5:4. Heat the solution at 60°C for 20 min while stirring continuously. After standing, filter it with suction and wash it with pure water until the filtrate is colorless. Then, dry the filter cake at 80°C for 12 h to obtain an orange-red product 2,3-diaminophenazine.
[0021] (2) Weigh o-phenylenediamine and p-hydroxybenzoquinone, then add H 2 O as solvent, the mixture is heated to 110°C under nitrogen atmosphere, and refluxed and stirred continuously for 10-12h. After the reaction is completed, it is cooled to room temperature, filtered to remove the solvent, washed with water, and vacuum dried to obtain a black powder, i.e., dihydroxyphenazine;
[0022] The molar ratio of o-phenylenediamine to p-hydroxybenzoquinone is 1:1 to 1:1.5.
[0023] (3) using the dihydroxyphenazine prepared in step (2) and the 2,3-diaminophenazine prepared in step (1) as raw materials, grinding until fully mixed, and heating to react to obtain a brown intermediate product;
[0024] The molar ratio of 2,3-diaminophenazine to dihydroxyphenazine is 1:1;
[0025] (4) Using the intermediate product prepared in step (3) to prepare a quinone-based organic electrode material with multiple active sites using a supercritical fluid method.
[0026] The specific preparation process of quinone-based organic electrode materials with multiple active sites using the supercritical fluid method is as follows:
[0027] The black intermediate product or brown intermediate product prepared in step (3) was added to 100 mL of anhydrous ethanol and ultrasonicated for 1 h to form a uniform dispersion. Then, K 2 Cr 2 O 7 The mixed solution was then sealed in a 0.5L stainless steel autoclave, the autoclave temperature was steadily raised to 30°C, and CO was then introduced into the autoclave. 2, so that the pressure in the autoclave reaches 6MPa. Then, slowly heat the autoclave to 130°C while stirring at a speed of 300r / min, so that the reaction system reaches a supercritical state. After the reaction lasts for 3 to 6 hours, cool the autoclave to room temperature and slowly release CO 2 After multiple washings and centrifugation, the product was dried in vacuum at 80°C to obtain a yellow solid product.
[0028] The above-mentioned conjugated quinonezine organic electrode material is used to prepare aqueous zinc ion battery electrode material.
[0029] The preparation method of the electrode material of the aqueous zinc ion battery is as follows: the conjugated quinonezine organic electrode material, the conductive additive and the binder are uniformly dispersed in a solvent and coated on a current collector, and vacuum dried to obtain an organic positive electrode. The mass ratio of the conjugated quinonezine organic electrode material, the conductive additive and the binder is 4 to 7:3 to 6:1.
[0030] The solvent is isopropanol or N-methyl-2-pyrrolidone (NMP), the current collector is 300 mesh stainless steel mesh, titanium mesh, carbon paper, aluminum foil or copper foil, the vacuum drying temperature is 60-80° C., and the drying time is 12-18 hours.
[0031] The assembly process of aqueous zinc-ion batteries is as follows: button cells are assembled in the order of anode shell, spring sheet, gasket, zinc sheet, glass fiber separator, electrolyte, cathode sheet and cathode shell. The assembled battery is sealed under high pressure using a button cell packaging machine and left to stand at room temperature until the electrolyte is fully infiltrated to obtain a zinc-ion battery.
[0032] Beneficial effects: The present invention designs a structurally diverse and stable conjugated quinonezine organic electrode material with multiple redox active sites and a uniform large π conjugated structure. The aqueous zinc ion battery assembled with the material has excellent actual specific capacity, material utilization, rate performance and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 is the hydrogen nuclear magnetic resonance spectrum of the organic electrode material I prepared in Example 1;
[0034] Figure 2 is a charge and discharge diagram of an aqueous zinc ion battery assembled with the organic electrode material prepared in Example 1;
[0035] Figure 3 The battery assembled in Example 1 was subjected to a current density of 5A g -1 The charge and discharge cycle life diagram below;
[0036] Figure 4is the infrared spectrum of Compound I benzo[b]quinoxalino[2,3-i]phenazine-6,8,13,15-tetraone of Example 2;
[0037] Figure 5 The battery assembled for Example 2 was operated at a current density of 0.05 A g -1 The charge and discharge cycle life diagram below;
[0038] Figure 6 The battery assembled for Example 3 was operated at a current density of 0.05 A g -1 The charge and discharge cycle life diagram below;
[0039] Figure 7 The battery assembled for Example 4 was operated at a current density of 0.05 A g -1 The charge and discharge cycle life diagram below;
[0040] Figure 8 The battery assembled for Control Example 1 was tested at a current density of 0.1 A g -1 The charge and discharge cycle life diagram below;
[0041] Fig. 9 The battery assembled for Control Example 1 was tested at a current density of 5A g -1 The charge and discharge cycle life diagram below. DETAILED DESCRIPTION
[0042] The present invention is further described in detail below in conjunction with the embodiments. The specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0043] Example 1: The synthesis route of organic electrode material I is as follows:
[0044]
[0045] (1) Weigh 10.07 g (45 mmol) of 2,3-dichloro-1,4-naphthoquinone and 16.70 g (90 mmol) of potassium phthalimide, add 150 ml of acetonitrile solution, heat to 80°C in an oil bath under nitrogen atmosphere, stir and reflux for 12 h. After the reaction, filter the hot product immediately, then wash with 500 ml of 80°C hot water and 200 ml of ethanol respectively. The filter cake obtained is a yellow solid 2,2'-(1,4-dioxane-1,4-dione-2,3-diyl)di(isoindoline-1,3-dione) (TPB), and then vacuum dry the product at 60°C for 12 h. Then add 16 g of TPB and 150 ml of hydrazine hydrate to a 250 ml single-necked flask, heat to 60°C in an oil bath, and reflux for 12 h. After the reactants were cooled to room temperature, the product was filtered and washed with ultrapure water 10 times until the filtrate was colorless, and the product was vacuum dried at 60° C. for 12 h to obtain dark purple solid 2,3-diamino-1,4-naphthoquinone.
[0046] (2) Weigh 0.5407 g (5 mmol) of o-phenylenediamine and 0.7 g (5 mmol) of p-hydroxybenzoquinone, then add 50 ml of H 2 O was used as solvent, and the mixture was heated to 110°C under nitrogen atmosphere, and refluxed and stirred for 12 hours. After the reaction was completed, it was cooled to room temperature, the suspension was filtered, the filter cake was washed with water, and vacuum dried at 80°C for 12 hours to finally obtain 0.576g of black powder, namely 2,3-dihydroxyphenazine.
[0047] (3) 0.429 g (2 mmol) of 2,3-diamino-1,4-naphthoquinone and 0.377 g (2 mmol) of 2,3-dihydroxyphenazine were ground in an agate mortar for 20 min until fully mixed. The mixture was then transferred to a porcelain boat, placed in a tube furnace, and heated at 400 °C for 4 h under a nitrogen atmosphere. After the reaction was completed, it was cooled to room temperature and 40 ml of acetone was added to form a slurry. The mixture was filtered and washed with 1-methylpyrrolidone (NMP) and ethanol successively until colorless, and then dried at 80 °C for 18 h to obtain a black intermediate product.
[0048] (4) The black intermediate product (0.63 g, 1.7 mmol) prepared in step (3) was added to 100 mL of anhydrous ethanol and ultrasonicated for 1 h to form a uniform dispersion. Then, 4 g (13.6 mmol) of K 2 Cr 2 O 7 The mixed solution was then sealed in a 0.5L stainless steel autoclave, the autoclave temperature was steadily raised to 30°C, and CO was then introduced into the autoclave. 2, so that the pressure in the autoclave reaches 6MPa. Under stirring at a speed of 300r / min, slowly heat the autoclave to 130℃ to make the reaction system reach a supercritical state. After the reaction lasts for 6h, the autoclave is cooled to room temperature and CO is slowly released. 2 , and the product was taken out. After washing 10 times and centrifugation, the product was vacuum dried at 80°C to finally obtain a yellow solid product, benzo[b]quinoxaline[2,3-i]phenazine-6,8,13,15-tetraone. The yield was 92.3%.
[0049] The solid product benzo[b]quinoxaline[2,3-i]phenazine-6,8,13,15-tetraone, conductive additive and binder were uniformly dispersed in solvent N-methyl-2-pyrrolidone (NMP) and coated (1.5 mg / cm 2 ) on a stainless steel mesh current collector and vacuum dried for 12 hours to obtain an organic positive electrode. The mass ratio of benzo[b]quinoxaline[2,3-i]phenazine-6,8,13,15-tetraketone, conductive additive and adhesive is 6:3:1. Button cells are assembled in the order of anode shell, shrapnel, gasket, zinc sheet, glass fiber diaphragm, electrolyte, cathode sheet (organic electrode material synthesized by the present invention) and cathode shell. The assembled battery is sealed under high pressure with a button cell packaging machine and allowed to stand at room temperature until the electrolyte is fully infiltrated to obtain a zinc ion battery.
[0050] Figure 1 This is the H NMR spectrum of Compound I benzo[b]quinoxalino[2,3-i]phenazine-6,8,13,15-tetraone in Example 1. It can be seen that Compound I has corresponding H NMR peaks at 8.51, 8.37, 8.20 and 8.05 ppm.
[0051] Figure 2 The battery assembled in Example 1 was -1 The charge and discharge curve under the voltage test window is 0.2V~1.5V. As can be seen from the figure, the organic electrode material has a high specific capacity (487mAh g -1 ) and discharge platforms (about 1.1V and 0.8V), and exhibited a coulombic efficiency close to 100%, showing the excellent electrochemical reversibility of the positive electrode material. At the same time, the organic electrode material has a good material utilization rate (91.9%).
[0052] Figure 3 The battery assembled in Example 1 was subjected to a current density of 5A g -1 The charge and discharge cycle life diagram under the condition of current density of 5A g -1 When the discharge capacity of the assembled battery is 365 mAh g -1 ; and 0.05Ag-1 Compared with the discharge capacity under the condition of 100 times higher than that under the condition of 100 times higher than that under the condition of 2 ... -1 The capacity retention rate is 92.3%; when the battery is cycled 5000 times, the discharge capacity is 318mAh g -1 , the capacity retention rate is 87.1%.
[0053] Example 2: The synthesis route of organic electrode material I is the same as that of Example 1. The specific preparation process is as follows:
[0054] (1) Weigh 10.07 g (45 mmol) of 2,3-dichloro-1,4-naphthoquinone and 16.70 g (90 mmol) of potassium phthalimide, add 150 ml of acetonitrile solution, heat to 80°C in an oil bath under nitrogen atmosphere, stir and reflux for 12 h. After the reaction, filter the hot product immediately, then wash with 500 ml of 80°C hot water and 200 ml of ethanol respectively. The filter cake obtained is a yellow solid 2,2'-(1,4-dioxane-1,4-dione-2,3-diyl)di(isoindoline-1,3-dione) (TPB), and then vacuum dry the product at 60°C for 12 h. Then add 16 g of TPB and 150 ml of hydrazine hydrate to a 250 ml single-necked flask, heat to 60°C in an oil bath, and reflux for 12 h. After the reactants were cooled to room temperature, the product was filtered and washed with ultrapure water for 10 times, and the product was vacuum dried at 60° C. for 12 h to obtain dark purple solid 2,3-diamino-1,4-naphthoquinone.
[0055] (2) Weigh 0.5407 g (5 mmol) of o-phenylenediamine and 1.05 g (7.5 mmol) of p-hydroxybenzoquinone, then add 50 ml of H 2 O was used as solvent, and the mixture was heated to 110°C under nitrogen atmosphere, and refluxed and stirred for 12 hours. After the reaction was completed, it was cooled to room temperature, the suspension was filtered, the filter cake was washed with water, and vacuum dried at 80°C for 12 hours to finally obtain 0.576g of black powder, namely 2,3-dihydroxyphenazine.
[0056] (3) 0.429 g (2 mmol) of 2,3-diamino-1,4-naphthoquinone and 0.566 g (3 mmol) of 2,3-dihydroxyphenazine were ground in an agate mortar for 20 min until fully mixed. The mixture was then transferred to a porcelain boat, placed in a tube furnace, and heated at 200 °C for 6 h under a nitrogen atmosphere. After the reaction was completed, the mixture was cooled to room temperature and 40 ml of acetone was added to form a slurry. The mixture was filtered and washed with 1-methylpyrrolidone (NMP) and ethanol successively until colorless, and then dried at 80 °C for 18 h to obtain a black intermediate product.
[0057] (4) The black intermediate product (0.635 g, 1.71 mmol) prepared in step (3) was added to 100 mL of anhydrous ethanol and ultrasonicated for 1 h to form a uniform dispersion. Then, 4 g (13.6 mmol) of K 2 Cr 2 O 7 The mixed solution was then sealed in a 0.5L stainless steel autoclave, the autoclave temperature was steadily raised to 30°C, and CO was then introduced into the autoclave. 2 , so that the pressure in the autoclave reaches 6MPa. Under stirring at a speed of 300r / min, slowly heat the autoclave to 130℃ to make the reaction system reach a supercritical state. After the reaction lasts for 6h, the autoclave is cooled to room temperature and CO is slowly released. 2 , and the product was taken out. After washing 10 times and centrifugation, the product was dried in vacuum at 80°C to finally obtain a yellow solid product, benzo[b]quinoxaline[2,3-i]phenazine-6,8,13,15-tetraone. The yield was 91.3%.
[0058] The solid product benzo[b]quinoxaline[2,3-i]phenazine-6,8,13,15-tetraone, conductive additive and binder were uniformly dispersed in solvent N-methyl-2-pyrrolidone (NMP) and coated (1.5 mg / cm 2 ) on a stainless steel mesh current collector and vacuum dried for 12 hours to obtain an organic positive electrode. The mass ratio of benzo[b]quinoxaline[2,3-i]phenazine-6,8,13,15-tetraketone, conductive additive and adhesive is 6:3:1. The button cell is assembled in the order of anode shell, shrapnel, gasket, zinc sheet, glass fiber diaphragm, electrolyte, cathode sheet and cathode shell. The assembled battery is sealed under high pressure with a button cell packaging machine and left to stand at room temperature until the electrolyte is fully infiltrated to obtain a zinc ion battery.
[0059] Figure 4 This is the infrared spectrum of the compound I of Example 2, benzo[b]quinoxalino[2,3-i]phenazine-6,8,13,15-tetraone. As can be seen from the figure, the compound I has a peak at 1710 cm -1 With 1590cm -1 There are two groups of strong absorption vibration peaks at 3490cm -1 The absorption vibration peak at is attributed to the OH bond of the water peak.
[0060] Figure 5 The battery assembled for Example 2 was operated at a current density of 0.05 A g -1 The charge and discharge cycle life diagram under the condition of current density of 0.05A g -1When the discharge capacity of the assembled battery is 469 mAh g -1 The utilization rate of the electrode material is 88.5%; when the battery is cycled 1000 times, the discharge capacity is 437mAh g -1 The capacity retention rate is 93.2%; when the battery cycles 2000 times, the discharge capacity is 423mAh g -1 , the capacity retention rate is 90.2%.
[0061] Example 3: The synthesis route of organic electrode material II is as follows:
[0062]
[0063] (1) Add 5.407g (50mmol) of o-phenylenediamine to a 1000ml beaker, then add 600ml of water, heat to 60°C, stir until completely dissolved, then add 6.488g of ferric chloride, add ultrapure water to 1000ml, stir for 20min, let stand overnight, pour out the supernatant, add ultrapure water to 1000ml, let stand for 12h, repeat three times. Wash with ultrapure water until the filtrate is colorless, then dry the filter cake at 80°C for 12h to obtain an orange-red product 2,3-diaminophenazine;
[0064] (2) The preparation process of 2,3-dihydroxyphenazine is the same as that of Example 1;
[0065] (3) 0.4244 g (2 mmol) of 2,3-diaminophenazine and 0.4205 g (2 mmol) of 2,3-dihydroxyphenazine were ground in an agate mortar for 20 min until fully mixed. The mixture was then transferred to a porcelain boat, placed in a tube furnace, and heated at 300 °C for 4 h under a nitrogen atmosphere. After the reaction was completed, the mixture was cooled to room temperature and 40 ml of acetone was added to form a slurry. The mixture was filtered and washed with acetone and ultrapure water successively until colorless, and then dried at 80 °C for 18 h to obtain a brown intermediate product.
[0066] (4) The brown intermediate product (0.386 g, 1 mmol) from step (3) was dissolved in 100 mL of glacial acetic acid and ultrasonicated for 1 h to form a uniform dispersion. Then, K 2 Cr 2 O 7 The mixed solution was then sealed in a 0.5 L stainless steel autoclave, the autoclave temperature was steadily raised to 30 °C, and CO was then introduced into the autoclave. 2 , so that the pressure in the autoclave reaches 6MPa. Under stirring at a speed of 300r / min, slowly heat the autoclave to 130℃ to make the reaction system reach a supercritical state. After the reaction lasts for 6h, the autoclave is cooled to room temperature and CO is slowly released. 2After washing 10 times and centrifugation, the product was dried in vacuum at 80°C to obtain a yellow solid product, pyrazino[2,3-b:5,6-b']dibenzo-6,17-dione, with a yield of 90.2%.
[0067] Figure 6 The battery assembled for Example 3 was operated at a current density of 0.05 A g -1 The charge and discharge cycle life diagram under the condition of current density of 0.05A g -1 When the discharge capacity of the assembled battery is 532 mAh g -1 , the utilization rate of battery materials is 87.2%; when the battery is cycled 1000 times, the discharge capacity is 485mAh g -1 , the capacity retention rate is 91.2%; when the battery cycles 5000 times, the discharge capacity is 457mAh g -1 , the capacity retention rate is 85.9%.
[0068] Example 4: The synthesis route of organic electrode material III is as follows:
[0069]
[0070] (1) First, add 6g (24.4mmol) of tetrachloronaphthoquinone and 20g (108mmol) of potassium phthalimide into a 250ml three-necked round-bottom flask, then add 150ml of acetonitrile solution, heat to 80℃ in an oil bath under nitrogen atmosphere, stir and reflux for 12h. Filter, wash with 500ml of 80℃ hot water and 200ml of ethanol, the filter cake obtained is yellow solid 2,2',2",2"'-(3,6-dioxocyclohexane-1,4-diene-1,2,4,5-tetrayl)tetra(isoindole-1,3-dione) (TCB), vacuum dry at 60℃ for 12h. Add 6g of TCB, 30ml of hydrazine hydrate and 10ml of ultrapure water into a 50ml single-necked flask, heat to 70℃ in an oil bath and react for 4h. The reactant was filtered while hot and washed 10 times with ultrapure water. The product was dried under vacuum at 80°C for 12 h to obtain a silvery purple solid 2,3,5,6-tetraaminobenzoquinone.
[0071] (2) The preparation process of 2,3-dihydroxyphenazine is the same as that of Example 1;
[0072] (3) 0.4244 g (2 mmol) of 2,3-diaminophenazine and 0.336 g (2 mmol) of tetraaminobenzoquinone were ground in an agate mortar for 20 min until fully mixed. The mixture was then transferred to a porcelain boat, placed in a tube furnace, and heated at 300 °C for 4 h under a nitrogen atmosphere. After the reaction was completed, the mixture was cooled to room temperature and 40 ml of acetone was added to form a slurry. The mixture was filtered and washed with acetone and ultrapure water successively until colorless, and then dried at 80 °C for 18 h to obtain a brown intermediate product.
[0073] (4) The brown intermediate product (0.520 g, 1 mmol) from step (3) was dissolved in 30 mL of glacial acetic acid and ultrasonicated for 1 h to form a uniform dispersion. Then, K 2 Cr 2 O 7 (4.412 g, 15 mmol), and then the mixed solution was sealed in a 0.5 L stainless steel autoclave, the autoclave temperature was steadily raised to 30 °C, and CO was then charged into the autoclave. 2 , so that the pressure in the autoclave reaches 6MPa. Then, under stirring at a speed of 300r / min, slowly heat the autoclave to 130℃ to make the reaction system reach a supercritical state. After the reaction lasts for 6h, the autoclave is cooled to room temperature and CO is slowly released. 2 , and the product was taken out. After washing 10 times and centrifugation, the product was vacuum dried at 80°C for 18 hours, and finally a yellow needle-shaped crystal product 6a,20a-pyrazino[2,3-b]pyrazino[2',3':6,7]quinoxalino[2,3-i]phenazine-6,8,10,17,19,21-hexanone was obtained. The yield was 88.7%.
[0074] In addition to being used as positive electrode materials for zinc ion batteries, quinonezine-based multi-active site organic materials are also not limited to their application in aqueous or organic lithium, sodium, potassium, magnesium, and aluminum ion batteries.
[0075] The organic electrode material ⅠII 6a,20a-pyrazino[2,3-b]pyrazino[2',3':6,7]quinoxalino[2,3-i]phenazine-6,8,10,17,19,21-hexanone was used as the positive electrode material of aqueous zinc ion batteries. Preparation of organic positive electrode for zinc ion battery: The organic positive electrode material, Ketjen black and polytetrafluoroethylene (mass ratio of 4.5:4.5:1) were evenly dispersed in NMP and evenly coated on carbon paper, followed by vacuum drying at 60°C for 4h and drying at 120°C overnight to obtain the organic positive electrode. Combined with the organic positive electrode, the zinc sheet was used as the negative electrode, the glass fiber membrane was used as the separator, and 2M ZnSO 4 The solution is an electrolyte, and the zinc ion battery is assembled, and the voltage test window is 0.2 V to 1.5 V. The assembled zinc ion battery is left to stand for 24 hours before the electrochemical test.
[0076] Figure 7 The battery assembled for Example 4 was operated at a current density of 0.05 A g -1 The charge and discharge cycle life diagram under the condition of current density of 0.05A g -1 When the discharge capacity of the assembled battery is 569 mAh g -1 , the utilization rate of battery materials is 87.5%; when the battery is cycled 1000 times, the discharge capacity is 502mAh g -1 , the capacity retention rate is 88.2%; when the battery cycles 5000 times, the discharge capacity is 469mAh g -1 , the capacity retention rate is 82.4%.
[0077] Comparative Example 1: Preparation of benzo[b]quinoxalino[2,3-i]phenazine-6,8,13,15-tetraone by liquid phase method
[0078] (1) The preparation process of 2,3-diamino-1,4-naphthoquinone and 2,3-dihydroxyphenazine is the same as that of Example 1;
[0079] (2) Using an agate mortar and pestle, 0.429 g (2 mmol) of 2,3-diamino-1,4-naphthoquinone and
[0080] 0.377 g (2 mmol) of 2,3-dihydroxyphenazine was ground in an agate mortar for 20 min until fully mixed, then the mixture was transferred to a porcelain boat, placed in a tube furnace, and heated at 280 ° C for 4 h under a nitrogen atmosphere. After the reaction was completed, it was cooled to room temperature and 40 ml of acetone was added to make a slurry. It was filtered and washed with 1-methylpyrrolidone (NMP) and ethanol successively until it was colorless, and then dried at 80 ° C for 18 h to obtain a black purple intermediate product.
[0081] (3) The above dark purple intermediate product (0.623 g, 1.7 mmol) was dissolved in 30 mL of glacial acetic acid, and then K 2 Cr 2 O 7 (4 g, 13.6 mmol), stirred and heated at 130 °C for 4 h, and cooled to room temperature after the reaction was completed. The suspension was filtered and the filter cake was washed with 1M H 2 SO 4 The product was washed and dried under vacuum at 80°C for 18 h to obtain yellow needle-shaped crystals of benzo[b]quinoxalino[2,3-i]phenazine-6,8,13,15-tetraone.
[0082] Figure 8 The zinc ion battery assembled for control example 1 was -1 Cycle life graph. The initial capacity is 375 mAh g -1After 100 cycles, the capacity of the organic zinc ion battery can still be maintained at 264 mAh g -1 , the capacity retention rate is 70.4%.
[0083] Fig. 9 The organic zinc ion battery assembled in Control Example 1 was -1 The cycle life diagram below. After 5000 cycles, the capacity of the organic zinc ion battery still remains at 100 mAh g -1 The capacity retention rate is about 61.2%.
[0084] Comparative Example 2:
[0085] 0.6407 g (4 mmol) of 2,3-dihydroxynaphthalene and 0.432 g (4 mmol) of o-phenylenediamine were ground in an agate mortar until fully mixed, and then the mixture was stirred and heated at 170 °C in a nitrogen atmosphere for 3 h. After cooling to room temperature, 40 mL of acetone was added to make a slurry, which was filtered and washed several times with deionized water and acetone, and then vacuum dried at 80 °C for 18 h to obtain a yellow solid.
[0086] The yellow solid (0.1161 g, 0.5 mmol) obtained above was dissolved in 15 mL of glacial acetic acid and K 2 Cr 2 O 7 (0.8825 g, 3 mmol), stirred and heated at 130 ° C for 3 h, and cooled to room temperature after the reaction was completed. The suspension was filtered, the filter cake was washed with deionized water and acetone, and vacuum dried at 80 ° C for 18 h to finally obtain a yellow needle-shaped crystal product with a yield of 86.1%. The capacity of the aqueous zinc ion battery assembled with this material is 282 mAh g -1 .
Claims
1. A quinone-based organic electrode material with multiple active sites, characterized in that: The quinone-based organic electrode material with multiple active sites is selected from one of benzo[b]quinoxalino[2,3-i]phenazine-6,8,13,15-tetraone (I), pyrazino[2,3-b:5,6-b']dibenzo-6,17-dione (II), and 6a,20a-pyrazino[2,3-b]pyrazino[2',3':6,7]quinoxalino[2,3-i]phenazine-6,8,10,17,19,21-hexanone (III):
2. A method for preparing a quinonezine organic electrode material with multiple active sites according to claim 1, characterized in that: The method for preparing the organic electrode material is: firstly, an amidation reaction is used to obtain an intermediate product, and then an oxidation method is used under a supercritical state to obtain a quinonezine organic electrode material with multiple active sites; wherein, the method for preparing the intermediate product is: an amidation reaction of dihydroxyphenazine and an o-phenylenediamine derivative or an amidation reaction of dihydroxyphenazine and 2,3-diaminophenazine is used to prepare the intermediate product.
3. The method for preparing the quinonezine organic electrode material with multiple active sites according to claim 2, characterized in that: The preparation steps of synthesizing quinone-based organic electrode materials using dihydroxyphenazine and o-phenylenediamine derivatives are as follows: (1) stirring and refluxing a naphthoquinone derivative and potassium phthalimide under a nitrogen atmosphere for 12 hours, filtering and washing with heat, adding hydrazine hydrate for reduction, washing and vacuum drying to obtain a solid o-phenylenediamine derivative; (2) Weighing o-phenylenediamine and p-hydroxybenzoquinone, then adding H2O as a solvent, heating the mixture under a nitrogen atmosphere for reaction, cooling to room temperature after the reaction is completed, filtering to remove the solvent, washing with water, and vacuum drying to obtain a black powder, i.e., dihydroxyphenazine; (3) using the dihydroxyphenazine prepared in step (2) and the o-phenylenediamine derivative prepared in step (1) as raw materials, grinding until fully mixed, and heating to react to obtain a black intermediate product; (4) Using the intermediate product prepared in step (3) to prepare a quinone-based organic electrode material with multiple active sites using a supercritical fluid method.
4. The method for preparing a quinonezine organic electrode material with multiple active sites according to claim 2, characterized in that: The preparation steps of synthesizing quinone-based organic electrode materials by reacting dihydroxyphenazine and 2,3-diaminophenazine are as follows: (1) o-phenylenediamine is dissolved in water, ferric chloride is added, and the solution is heated at 60°C for 20 minutes under constant stirring; after standing, the solution is filtered and then washed with pure water until the filtrate is colorless, and then the filter cake is dried at 80°C for 12 hours to obtain an orange-red product 2,3-diaminophenazine; (2) Weighing o-phenylenediamine and p-hydroxybenzoquinone, then adding H2O as a solvent, heating the mixture under a nitrogen atmosphere for reaction, cooling to room temperature after the reaction is completed, filtering to remove the solvent, washing with water, and vacuum drying to obtain a black powder, i.e., dihydroxyphenazine; (3) using the dihydroxyphenazine prepared in step (2) and the 2,3-diaminophenazine prepared in step (1) as raw materials, grinding until fully mixed, and heating to react to obtain a brown intermediate product; (4) Using the intermediate product prepared in step (3) to prepare a quinone-based organic electrode material with multiple active sites using a supercritical fluid method.
5. The method for preparing the quinonezine organic electrode material with multiple active sites according to claim 3 or 4, characterized in that: In step (1), the molar ratio of the naphthoquinone derivative to the potassium salt of phthalimide is 1:2-1:4.5, the naphthoquinone derivative is selected from 2,3-dichloro-1,4-naphthoquinone or tetrachloronaphthoquinone; the molar ratio of o-phenylenediamine to ferric chloride is 5:
4.
6. The method for preparing a quinonezine organic electrode material with multiple active sites according to claim 3 or 4, characterized in that: In step (2), the molar ratio of o-phenylenediamine to p-hydroxybenzoquinone is 1:1 to 1:1.5; the reaction conditions are: continuous reflux stirring at 110° C. for 10 to 12 hours.
7. The method for preparing a quinonezine organic electrode material with multiple active sites according to claim 3 or 4, characterized in that: In step (3), the molar ratio of dihydroxyphenazine to o-phenylenediamine derivative is 1:1 to 1:1.5; the heating reaction temperature is 200 to 400° C., and the heating reaction time is 4 to 6 hours; the molar ratio of 2,3-diaminophenazine to dihydroxyphenazine is 1:
1.
8. The method for preparing a quinonezine organic electrode material with multiple active sites according to claim 3 or 4, characterized in that: In step (4), the preparation process of the quinone-based organic electrode material with multiple active sites is as follows: the black intermediate product or the brown intermediate product prepared in step (3) is added to anhydrous ethanol, ultrasonically formed into a uniform dispersion, then K2Cr2O7 is added, and then the mixed solution is sealed in a stainless steel autoclave, the temperature of the autoclave is raised to 30°C, CO2 is then charged into the autoclave to make the pressure in the autoclave reach 6MPa, and then the autoclave is heated to 130°C while stirring at a speed of 300r / min to make the reaction system reach a supercritical state. After the reaction continues for 3 to 6 hours, the autoclave is cooled to room temperature, CO2 is released, and the product is taken out; after washing and centrifugation, the product is vacuum dried at 80°C to finally obtain a yellow solid product.
9. An application of the quinonezine organic electrode material with multiple active sites according to claim 1, characterized in that: The quinonezine organic electrode material with multiple active sites is used to prepare an aqueous zinc ion battery electrode material, wherein the electrode material preparation method comprises: uniformly dispersing the quinonezine organic electrode material, a conductive additive and a binder in a solvent and coating the same on a current collector, and vacuum drying the same to obtain an organic positive electrode; the mass ratio of the quinonezine organic electrode material, the conductive additive and the binder is 4 to 7:3 to 6:
1.
10. The use of the quinonezine organic electrode material with multiple active sites according to claim 9, characterized in that The assembly process of the aqueous zinc ion battery is as follows: assembling button cells in the order of anode shell, spring sheet, gasket, zinc sheet, glass fiber diaphragm, electrolyte, cathode sheet and cathode shell; sealing the assembled battery under high pressure with a button cell packaging machine, and standing at room temperature until the electrolyte is fully infiltrated to obtain a zinc ion battery.
Citation Information
Patent Citations
5,7,12,14-tetranitrogen-6,13-pentacenequinone-based electrode material as well as preparation method and application thereof
CN108864104A
High-capacity metal ion battery organic electrode material, and preparation method and application thereof
CN112961163A
Conjugated quinone azine organic electrode material and preparation method and application thereof
CN114497547A
Zinc ion total battery without zinc metal
CN117039204A
Photoelectric conversion element, material for photoelectric conversion element, and compound
JP2024117715A
Cited By
N-heterocyclic organic electrode material, preparation method thereof and aqueous aluminum ion battery
CN119241544A
Hydroxyl-containing multi-active-site quinone organic electrode material and application thereof in metal zinc ion battery
CN120965598A
